2016
DOI: 10.26905/jkdp.v20i3.287
|View full text |Cite
|
Sign up to set email alerts
|

Uji Empiris Model Asset Pricing Lima Faktor Fama-French Di Indonesia

Abstract: The main purpose of this study is to evaluate and compare the performances of the Fama-French three-(FF3) and five-factor (FF5) models in the Indonesia stock market. This study also examines whether book-to-market factor (HML) is redundant in explaining the portfolio excess returns in Indonesia. This study employs asset pricing factor of the 2 x 3 sorts and excess returns of 25 Size-B/M, 25 Size-OP, dan 25 Size-Inv portfolios as dependent variables. This study employs Ordinary Least Square (OLS) with monthly t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
12
0
4

Year Published

2019
2019
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(24 citation statements)
references
References 16 publications
8
12
0
4
Order By: Relevance
“…On the other hand, companies with high ratios will reflect inefficient market conditions which also will expose risk for investors. Sutrisno and Ekaputra (2016) and Fama and French (2015) also mentioned that book-to-market which is proxied by High Minus Low (HML) has a positive relationship to stock portfolio excess returns. H3: book-to-market equity has a positive effect on ISSI's stock portfolio excess return.…”
Section: Size and Its Effect On Stock Portfolio Excess Returnsmentioning
confidence: 99%
See 3 more Smart Citations
“…On the other hand, companies with high ratios will reflect inefficient market conditions which also will expose risk for investors. Sutrisno and Ekaputra (2016) and Fama and French (2015) also mentioned that book-to-market which is proxied by High Minus Low (HML) has a positive relationship to stock portfolio excess returns. H3: book-to-market equity has a positive effect on ISSI's stock portfolio excess return.…”
Section: Size and Its Effect On Stock Portfolio Excess Returnsmentioning
confidence: 99%
“…The higher the company's profit, the higher the rate of return obtained by investors is. Profitability which is proxied by Robust Minus Weak (RMW) is the difference between the average return on two portfolios that have high operating profitability and the average return on two portfolios that have low operating profitability every month (Sutrisno & Ekaputra 2016). Research by Fama and French (2015) and Chiah, Chai, and Zhong (2015) indicated that profitability has a positive relationship with the return.…”
Section: Rmw Profitability and Its Effect On Stock Portfolio Excess Returnsmentioning
confidence: 99%
See 2 more Smart Citations
“…22 years after the threefactor Fama-French model was developed, Fama and French introduced the model by adding two other factors namely profitability and investment [2]. It has been shown that the Fama-French Five Factor Model describes the variation in portfolio returns better than the three-factor model, although profitability and investment factors have only weak effects on excess returns [17].…”
Section: Literature Review a The Journey Of Asset Pricing Modelmentioning
confidence: 99%